Photodegradation of Diquat and Paraquat in aqueous solutions by titanium dioxide: evolution of degradation reactions and characterisation of intermediates - Florêncio, M.Helena; Pires, Elisabete; Castro, Ana L; Nunes, Manuel R; Borges, Carlos; Costa, Fernanda M (Chemosphere (Oxford), 2004)
The titanium dioxide assisted photodegradation of Diquat and Paraquat herbicides solutions has been the subject of the present investigation, considering its direct application in the treatment of contaminated waters and soils. To have a better understanding of the photodegradation process, different types of TiO 2, commercial and ‘home prepared’ Ti 1− x Fe x O 2 ( x=0% and 4%), were used as catalysts, using an UV light as radiation source. The degradation reactions were followed by UV spectroscopy and the intermediates and reaction products were characterised by electrospray ionisation mass spectrometry (ESIMS) combined with collision-induced dissociation (CID) and tandem mass spectrometry (MS/MS). The present study shows that, for photocatalytic degradation of Diquat and Paraquat solutions, a basic pH can be determinant, as well as the type of catalyst. The type of catalyst can also strongly influence the degradation pattern of the herbicide. Regarding complete degradation, we were able to show that Diquat is more persistent than Paraquat. During the photocatalytic processes, several intermediate and reaction products are sequentially formed, to which structures are proposed.